(Trans)gender citizenship in Italy: a contradiction in terms? From the parliamentary debate about Law 164/1982 to the present. Issue 2 (23rd April 2018) - Voli, Stefania
Abstract : This article concerns the processes of normalisation and medicalisation of transgender people's experiences in Italy. Drawing on the analysis of the parliamentary debate which led to the endorsement of Law no. 164/1982, 'Rules Concerning the Rectification of Sex-Attribution', the article will foreground the (still) existing contradictions between trans people's (ostensible) individual rights over their own gendered bodies, as enshrined in law, and their subjection to medico-legal supervision and control. Next, it will look at the relationship between transgender experience and the notion of citizenship: in particular, it will explore the opportunities and contradictions in the possibility of trans citizenship in the current Italian context. Italian summary: Questo articolo discute i processi di normalizzazione e medicalizzazione delle esperienze delle persone transgender in Italia. A partire dall'analisi del dibattito parlamentare che ha condotto all'approvazione della Legge 164/1982 'Norme in materia di rettificazione di attribuzione di sesso', esso porterà in primo piano le contraddizioni che (tuttora) esistono tra (gli apparenti) diritti individuali delle persone trans sui loro corpi gendered, così come sancito dalla legge, e il loro assoggettamento alla supervisione ed al controllo medico-legale. Guardando alla relazione tra l'esperienza transgender e la nozione di cittadinanza, l'articolo analizza nella seconda parte opportunità e contraddizioni di una 'cittadinanza trans' nell'attuale contesto italiano.